2017
DOI: 10.22146/bkm.27301
|View full text |Cite
|
Sign up to set email alerts
|

Kesiapsiagaan rumah sakit umum Kabanjahe dalam menaggulangi bencana alam gempa bumi di Kabupaten Karo

Abstract: Obstacles and opportunities in making a hospital disaster plan: the case study from North SumateraPurposeThis study assessed Kabanjahe District hospital preparedness in coping with earthquake disaster, describes obstacles and opportunities in forming hospital disaster preparedness and availability of hospital disaster plan component.MethodsThis research used qualitative research method with case study research design. This study examines the contemporary phenomenon of Kabanjahe General Hospital preparedness in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on the latest test for cholinesterase activity data conducted in 2008, it was found that there was pesticide toxicity in farmers in several regions scattered in Karo District with an average of 55.26-91.25% of all [15]. Some cases handled by Kabanjahe General Hospital occurred as many as 21 cases starting from January to October 2017, generally caused by ingestion of herbicides, pesticides Gramaxone, and Roundup [16]. This percentage shows that the risk of toxicity is very high in pesticides used by farmers in the Karo communities.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the latest test for cholinesterase activity data conducted in 2008, it was found that there was pesticide toxicity in farmers in several regions scattered in Karo District with an average of 55.26-91.25% of all [15]. Some cases handled by Kabanjahe General Hospital occurred as many as 21 cases starting from January to October 2017, generally caused by ingestion of herbicides, pesticides Gramaxone, and Roundup [16]. This percentage shows that the risk of toxicity is very high in pesticides used by farmers in the Karo communities.…”
Section: Introductionmentioning
confidence: 99%